Fistelografy dengan Sangkaan Vesico Perianal Fistel di Rumah Sakit Umum Daerah Dr. Pirngadi Medan - Lubis, Hotben; Ariyanti, Stephanie (Health Information : Jurnal Penelitian, 2023)
This is an examination of abnormal holes (fistels) using X-rays, which can clearly determine the fistula. Fistelography examination with suspected Vesico perianal fistula aims to get a picture of the relationship of the abnormal hole (fistel) with other organs, from postero-anterior and lateral projections, contrast media is needed so that it can show the relationship of the abnormal hole (fistel) with other organs. This research uses descriptive and qualitative types. The research was carried out in July 2020 at the Dr. Pirngadi Medan Regional General Hospital using a General X-ray unit. Data collection techniques using 1. Interview with a radiographer, 2. Observation, namely carrying out examinations on patients undergoing fistelography examinations with suspected vesico perianal fistula, by recording and documenting the results of the examination. 3. Documentation of the results of the processed data and the results are transcribed and copied in typed form. From the research results, contrast is obtained, sharpness of detail of the criteria covering the object. The film recording used is Computer Radiography (CR).